(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The purpose of the research: The article reveals the parameters of artistic inclusive secondary education Research methods: The following research methods were used: analysis, synthesis, comparison, observation and statistics. Research results: Research has revealed insufficient coverage of children with disabilities in secondary art education in Uzbekistan Practical application: Development of methodological manuals for the timely identification, awareness and referral of talented children to secondary educational institutions with an artistic bias.